The Role of the Job Creation Law in Increasing Investment and Labor Protection in Indonesia - Asriadi Asriadi; Abdullah Sulaiman (Publikasi Indonesia, 2025)
The revision of the Job Creation Law through Law Number 6 of 2023 aims to improve the investment climate and protection of workers in Indonesia. These regulatory changes include simplifying business licensing through the Online Single Submission (OSS) system, implementing risk-based licensing, and incentivizing investors to attract more domestic and foreign investment. From the employment aspect, this revision introduces adjustments to the minimum wage formula, restrictions on the outsourcing sector, changes to severance pay provisions, and more structured termination of employment (PHK) procedures. The Job Loss Guarantee (JKP) program is delivered as additional protection for laid-off workers. Although this policy provides legal certainty and flexibility for the business world, the main challenges in its implementation are the supervision of company compliance, the effectiveness of labor protection, and the readiness of the bureaucracy to implement a more transparent system. With a normative legal approach through regulatory analysis, this study highlights the impact of changes to the Job Creation Law on investment and employment. It provides recommendations to strengthen supervision, socialization, and collaboration between the government, the business world, and workers. The policy is expected to create a competitive investment environment, improve worker welfare, and encourage inclusive and sustainable economic growth in Indonesia.